TRANSAKSI JUAL BELI DALAM PENDIDIKAN ISLAM - Destri Wulandari; Dwi Noviana; Atika Septina (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2023)
The practice of buying and selling has existed since the time of Rasullulah SAW, starting from very simple buying and selling practices and even buying and selling that uses sophisticated tools that have been created by humans from time to time. Islam is very concerned about the elements of buying and selling. This study aims to emphasize that no matter how sophisticated the transaction tools that have developed at this time, buying and selling transaction must comply with the provisions of buying and selling in Islam. The writing approach used in this writing uses library research. In writing this explains the meaning of buying and selling, the legal basis of buying and selling, the three pillars and conditions of buying and selling, khiyar in buying and selling and buying and selling which are prohibited in Islam.